Argument Evaluation: If your Snark be a Boojum… An Essay in Three Fits - Hinton, Martin (Informal Logic, 2024)
In this essay, I make a plea for a wide-ranging, open perspective on the evaluation of arguments. This involves a more flexible understanding of what fallacies are and for what arguments may be used. I acknowledge the great wealth of argumentation theory, but bemoan the lack of systematic, repeatable, and explainable evaluation procedures. I then go on to introduce the works which contribute to this special issue and explain how they assist in the fulfilment of my hopes.